EFEKTIVITAS PEMBELAJARAN REMEDIAL DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS DI MTs NEGERI 1 PALU - N. Samani, Moh. Israwan; Pettalongi, Adawiyah; Nur, Rizka Fadliah (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2022)
This article discusses the effectiveness of remedial learning in improving student learning outcomes in social studies subjects at MTs Negeri 1 Palu. The focus of the discussion in this study is how the effectiveness of remedial learning in improving student learning outcomes in social studies subjects at MTs Negeri 1 Palu and what factors hinder Remedial Learning in improving student learning outcomes in social studies subjects at MTs Negeri 1 Palu. The method that the author uses in this study is a qualitative research method. With data collection techniques including observation, interviews, and documentation. The results of this study indicate that in the effectiveness of remedial learning in improving student learning outcomes in social studies subjects at MTs Negeri 1 Palu, namely efforts to improve students are carried out if these students have not reached the minimum standard value, then students will be given remedial. because in this remedial learning students only repeat material that is not understood. Then the inhibiting factors in the effectiveness of remedial learning in improving student learning outcomes in social studies subjects at MTs Negeri 1 Palu, namely, the lack of attention from students, limited learning time carried out in schools as a result of the pandemic that is still endemic and the lack of communication between teachers and students. students to the problem of improving the value and efficiency of remedial learning in schools.